Supervision as a Kind of Qualitative Evaluation - Riva, Maria Grazia; Ratsika, Nikoleta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The contribution presents a reflection on supervision as one of the possible forms of qualitative evaluation, in the field of work with adult educators. Supervision structures a context where theory and practice, emotions and cognitions, values, representations and fears, anxieties and conflicts can be made to dialogue in continuation. The supervisor continuously offers feedback and interpretations to the educators, thanks to attentive listening and decodes what they express. The constructivist approach to Evaluation, on the one hand, gives full value to the subjectivity of the actors involved in the evaluation process and aims to interpret and understand. So, we can call it hermeneutic evaluation (Perla, 2004). Hermeneutic evaluation sets the problem of finding the meaning of the points of view of the participants. This is where the meeting point with the supervision activity, which consists precisely of a practice guided by a leader who helps the educators to better understand their theoretical frameworks of reference and their basic educational models, lies. Supervision and Evaluation therefore represent two important tools for developing the professionalism of the operators, as shown by the case-study analyzed. The practice of supervision is part of a path of  lifelong learning and education (Oggionni, 2013; Zannini, 2005), which passes through experimentation, evaluation and redesigning, in the face of constant monitoring of the needs and learning of the individual and of the team.